Validez de contenido por juicio de expertos de un instrumento para medir percepciones físico-emocionales en la práctica de disección anatómica (2023)
Introduction: The objective of the present investigation was to carry out content validity based on expert judgment of a measurement instrument that investigates 4 dimensions: physical reactions, consequences, disturbances and coping methods of students of medicine before the practice of anatomical dissection. Material and method: Psychometric study of content validity, in which 9 experts participated who evaluated each item based on the characteristics of sufficiency, clarity, coherence, relevance and pertinence, as well as estimates related to the congruence of the items, breadth of content, writing, clarity and relevance of the original instrument. The qualitative observations of the experts were taken into account. The degree of agreement between experts was determined with the Fleiss kappa coefficient. A preliminary test was applied to measure the degree of comprehensibility. Results: Globally, almost perfect strength of agreement was obtained in each dimension, and in pairs of experts, between moderate and almost perfect. For the characteristics, the relevance was the highest (0.8443) and in the statistical significance, the sufficiency (p =.0268). The structure of the instrument was adjusted, without affecting the content validity. Of the 39 original items, 16 items were eliminated, and 22 items were retained, of which 6 were corrected in writing. The degree of comprehensibility was of high rank for the new version of the instrument. Conclusion: The validated instrument can be explored and applied to favor the comparison of populations of different faculties in this and other countries that speak the same Spanish language. © 2018 Elsevier España, S.L.U.